Neologizmy słowotwórcze w Obserwatorium Językowym Uniwersytetu Warszawskiego (na materiale haseł opracowanych do lutego 2022 roku). Część 2: Substantywne derywaty złożone - Rybarski, Mateusz (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2024)
This article constitutes the second part of a series of papers devoted to 1117 Polish derivational neologisms in Obserwatorium Językowe Uniwersytetu Warszawskiego (Language Obserwatory of the University of Warsaw). Its aim is to present and analyse 334 new substantival compounds in the Polish language. The author divides them into groups of derivational neologisms created by the use of the same formative technique and containing the same part of the compound. The study concludes that the biggest class of the described new substantival compounds in contemporary Polish language consists of structures without any affixes. As for the morphemes used to create them, the interfix -o- turned out to be the most productive. Most of them contain the elements e- (abbreviated adjective elektroniczny [electronic]) and -mat (abbreviated noun automat).